(untitled) (Homoeopathy for All, 2025)
With millions of fresh cases detected every year, the worldwide cancer load is increasing. Though life-saving, the harsh treatment approaches, including radiotherapy and chemotherapy, often compromise the psychological and physical well-being of patients. Chemotherapy-induced nausea and vomiting (CINV) represents one of the most prevalent and concerning adverse events encountered by cancer patients. CINV is linked resulting in considerable morbidity that adversely impacts the quality of life for patients. The occurrence is fundamentally influenced by the dosage and specific type of chemotherapy agent utilized in the treatment. These symptoms not only lower quality of life (QoL) but also cause treatment delays, decreased adherence to chemotherapy regimens, and higher healthcare expenses. Not only does managing the side effects of these treatments help to maintain QoL, but it also guarantees that patients may finish their therapy courses without interruption. Although many people find relief from traditional antiemetic treatments, they are not always successful and could cause side effects. With its individualised approach and low side-effect profile, homeopathy has become a supporting therapy option for controlling nausea and vomiting caused due to chemotherapy.